Clinical geneticists' views on and experiences with unsolicited findings in next‐generation sequencing: "A great technology creating new dilemmas". Issue 2 (11th November 2022) - van der Schoot, Vyne; Damsté, Carlijn; Yntema, Helger G.; Brunner, Han G.; Oerlemans, Anke J. M.
Abstract: Unsolicited findings (UFs) from diagnostic genetic testing are a subject of debate. The emerging consensus is that some UFs from genetic testing should be disclosed, but recommendations on UF disclosure generally leave room for variation in practice. This study aimed to explore clinical geneticists' views on and experiences with UFs during pretest counseling and UF disclosure. We interviewed 20 certified clinical genetics medical specialists and clinical genetics residents, working in 7 Dutch genetic centers. Participants indicated that discussing the probability of detecting UFs is an integral part of pretest counseling and informed consent. However, they expressed doubts about the degree to which this discussion should occur and about what information they should share with patients. They argued that the contents of their counseling should depend on the individual patient's capacity to understand information. These results endorse the importance of tailored pretest counseling alongside informed consent for optimal genetic consultations. While "medical actionability" is broadly accepted as an important criterion for the disclosure of UFs, participants experienced substantial uncertainty regarding this concept. This study underscores the need for further demarcation of what exactly constitutes medical actionability. Installation of an expert panel to help healthcare professionals decide what variants to disclose will support them when facing the dilemmas presented by UFs.